1838 R.I. Pub. Laws 3-5 (Jan. Sess.), An Act Concerning Crimes and Punishments. - (:unkn) unknown (General Publisher, 1838)
Every person who shall be convicted of voluntarily engaging in a duel, with any dangerous weapon, to the hazard of life, shall be imprisoned not exceeding seven years, nor less than one year. § 7. Every person who shall be convicted of challenging another to fight a duel with any with any dangerous weapon to the hazard of life, and every person who shall be convicted of accepting any challenge to fight such duel, though no duel be fought, shall be imprisoned not exceeding seven years nor less than one year.
--
Keywords: DUELING